CRIMINOLOGICAL ASPECTS OF VIOLENCE AND ABUSE OF CHILDREN (Journal of actual problems of jurisprudence, 2025)
This article presents current aspects of violence and abuse against children. In particular, attention is drawn to the issues of prevention and warning of violence, abuse against children, offenses and crimes, neglect and homelessness among minors.At the same time, issues of combating crime against minors and juvenile delinquency should include a range of measures of an economic, political, social and legal nature.In order to ensure the safety of children, it was concluded that work in this direction should be carried out step by step, consistently by identifying sources of threats, studying, analyzing the causes and conditions, determining the scale and consequences.In order to reduce the number of children and adolescents actively involved in illegal content, a number of new initiatives are proposed, including legislative ones.The article contains tasks and conclusions, the possibility of their practical implementation, the conclusions and proposals formulated in the work can find practical application in the activities of employees of authorized state and law enforcement agencies in the field of protecting children's rights.Financing. The scientific article was prepared within the framework of program-targeted funding for scientific and (or) scientific and technical programs for 2023-2025, aimed at implementing the project IRN BR 21882414 “Program for the support and rehabilitation of child victims of violence: practical implementation of a network of modular resource centers”, financed by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan.Keywords: children, safety, injuries, prevention, crime, offense, violence, abuse, dysfunctional family, cyberbullying.